VESPA: A community-driven Virtual Observatory in Planetary Science. (January 2018) - Erard, S.; Cecconi, B.; Le Sidaner, P.; Rossi, A.P.; Capria, M.T.; Schmitt, B.; Génot, V.; André, N.; Vandaele, A.C.; Scherf, M.; Hueso, R.; Määttänen, A.; et al.
Abstract: The VESPA data access system focuses on applying Virtual Observatory (VO) standards and tools to Planetary Science. Building on a previous EC-funded Europlanet program, it has reached maturity during the first year of a new Europlanet 2020 program (started in 2015 for 4 years). The infrastructure has been upgraded to handle many fields of Solar System studies, with a focus both on users and data providers. This paper describes the broad lines of the current VESPA infrastructure as seen by a potential user, and provides examples of real use cases in several thematic areas. These use cases are also intended to identify hints for future developments and adaptations of VO tools to Planetary Science. Highlights: VESPA distributes and searches data related to Solar System studies according to the Virtual Observatory (VO) paradigm. The current status of the VESPA is described: Uses case are presented to illustrate the usage of the search interface and tools.